Faktor-Faktor yang Memengaruhi Empati pada Mahasiswa Kedokteran - Alifah, Rahmah; Lisiswanti, Rika; Ratna, Maya Ganda; Oktafany (CV. Jasa Sukses Abadi, 2024)
Empathy in medical students is an important aspect that affects how medical students interact with patients and understand their feeling. In the medical world, empathy can enhance the doctor-patient relationship, improve patient satisfaction, and can even affect clinical outcomes. Patients who feel empathy from their doctors are more likely to fully explain their symptoms and actively engage in the doctor-patient relationship. Research shows that empathetic doctors tend to have more satisfied and compliant patients. A number of studies have identified that the level of empathy in medical students varies and is influenced by several factors. The purpose of this literature review is to identify the factors that affect empathy in medical students. The journal were obtained from Google Scholar and Pubmed database with keyword (Empathy) and (Medical Student) for publication in 2015-2024. Journal inclusion criteria used were medical student population, journals that discussed the relationship between several factors with empathy levels, and published between 2015-2024. Exclusion criteria are journals that cannot be accessed completely. The method of analysis carried out in this literature review is a descriptive method, which describes and explains through narratives of the articles found. Based on the results of review from several journals, it was found that factors such as stress, role models, empathy training, mental health, self-control, self-motivation, social awareness, and social skills, perception of learning environment, personality, self-reflection, emotional intelligence, and gratitude.